Sharing the Fruit of Labor: Flexible Application of Justice Principles in an Ultimatum Game with Joint-Production. - Bediou, Benoit; Sacharin, Vera; Hill, Christopher; Sander, David; Scherer, Klaus (Social Justice Research, 2012)
Individuals often need to negotiate how to distribute jointly produced goods-equally (e.g., 50:50) or equitably (e.g., proportionally to their contributions). We examined whether people have stable preferences, or whether they switch between equality and equity in different situations. Pairs of anonymous participants first produced a common pie, and then distributed it in an ultimatum game. Results suggest that individuals apply different justice principles depending on their contribution. When they produced less than 50%, proposers divided the pie equally. However, when they produced more than 50%, their offers fell between equality and equity. Responders' ratings of fairness and satisfaction varied similarly; with low production, equality was preferred, whereas with high production, equity was preferred. Nevertheless, equal and equitable offers were generally accepted, and only outright unfair offers were rejected. This suggests that individuals are relatively flexible about which justice principle should be applied, but punish proposers whose offers violate both principles.